Age and Sex Influence the Neuro-inflammatory Response to a Peripheral Acute LPS Challenge - Murtaj, Valentina; Belloli, Sara; Di Grigoli, Giuseppe; Pannese, Maria; Ballarini, Elisa; Rodriguez-Menendez, Virginia; Marmiroli, Paola; Cappelli, Andrea; Masiello, Valeria; Monterisi, Cristina; Bellelli, Giuseppe; Panina-Bordignon, Paola; et al. (Frontiers in Aging Neuroscience, 2019)
Aging is associated with an exaggerated response to peripheral inflammatory challenges together with behavioral and cognitive deficits. Studies considering both age and sex remain limited, despite sex dimorphism of astrocytes and microglial cells is largely recognized. To fill this knowledge gap, we investigated the effect of a single intraperitoneal lipopolysaccharide (LPS) administration in adult and aged mice. We assessed the expression of different inflammatory mediators, and the microglial response through binding of [18F]-VC701 tracer to translocator protein (TSPO) receptors in the male and female brain. Aged female brain showed a higher pro-inflammatory response to LPS compared to adult female and to aged male, as revealed by ex vivo binding to TSPO receptors and pro-inflammatory mediator transcript levels. The highest astroglial reaction was observed in the brain of aged females. Differently to the other groups of animals, in aged males LPS challenge did not affect transcription of triggering receptor expressed on myeloid cells 2 (TREM2). In conclusion, our study shows that in the mouse brain the neuroinflammatory response to an acute peripheral insult is sex and age dependent. Moreover, our results might set the basis for further studies aimed at identifying sex related targets involved in the modulation of the aberrant neuro-inflammatory response that characterizes aging. This knowledge could be relevant for the treatment of conditions such as delirium and dementia.